2021
DOI: 10.15282/ijsecs.7.1.2021.6.0082
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Accuracy of Static Source Code Based Software Change Impact Analysis Through Hybrid Techniques: A Review

Abstract: Change is an inevitable phenomenon of life. This inevitability of change in the real world has made a software change an indispensable characteristic of software systems and a fundamental task of software maintenance and evolution. The continuous evolution process of software systems can greatly affect the systems’ quality and reliability if proper mechanisms to manage them are not adequately provided. Therefore, there is a need for automated techniques to effectively make an assessment of proposed software ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Wiese [29] found that contextual information, such as commit metadata and developer communication, can significantly enhance prediction models, reducing false recommendations. Similarly, Shakirat [30] reviewed hybrid techniques for software change impact analysis, highlighting their potential to enhance accuracy. These studies and others such [31], [32] that leveraged hybrid approaches to change-prone prediction collectively underscore the potential of hybrid approaches in improving the accuracy of software co-change prediction.…”
Section: Related Workmentioning
confidence: 99%
“…Wiese [29] found that contextual information, such as commit metadata and developer communication, can significantly enhance prediction models, reducing false recommendations. Similarly, Shakirat [30] reviewed hybrid techniques for software change impact analysis, highlighting their potential to enhance accuracy. These studies and others such [31], [32] that leveraged hybrid approaches to change-prone prediction collectively underscore the potential of hybrid approaches in improving the accuracy of software co-change prediction.…”
Section: Related Workmentioning
confidence: 99%